Conservation of AtTZF1, AtTZF2, and AtTZF3 homolog gene regulation by salt stress in evolutionarily distant plant species - D’Orso, Fabio; De Leonardis, Anna M.; Salvi, Sergio; Gadaleta, Agata; Ruberti, Ida; Cattivelli, Luigi; Morelli, Giorgio; Mastrangelo, Anna M. (Frontiers in Plant Science, 2015)
Arginine-rich tandem zinc-finger proteins (RR-TZF) participate in a wide range of plant developmental processes and adaptive responses to abiotic stress, such as cold, salt and drought. This study investigates the conservation of the genes AtTZF1-5 at the level of their sequences and expression across plant species. The genomic sequences of the two RR-TZF genes TdTZF1-A and TdTZF1-B were isolated in durum wheat and assigned to chromosomes 3A and 3B, respectively. Sequence comparisons revealed that they encode proteins that are highly homologous to AtTZF1, AtTZF2 and AtTZF3. The expression profiles of these RR-TZF durum wheat and Arabidopsis proteins support a common function in the regulation of seed germination and responses to abiotic stress. In particular, analysis of plants with attenuated and overexpressed AtTZF3 indicate that AtTZF3 is a negative regulator of seed germination under conditions of salt stress. Finally, comparative sequence analyses establish that the RR-TZF genes are encoded by lower plants, including the bryophyte Physcomitrella patens and the alga Chlamydomonas reinhardtii. The regulation of the Physcomitrella AtTZF1-2-3-like genes by salt stress strongly suggests that a subgroup of the RR-TZF proteins has a function that has been conserved throughout evolution.